Animal models of osteoporosis - LELOVAS (Π. ΛΕΛΟΒΑΣ) P. (Journal of the Hellenic Veterinary Medical Society, 2017)
Osteoporosis is an important systemic disorder, affecting mainly Caucasian women, with a diverse and multifactorial aetiology. A large variety of animal species, such as rodents, rabbits, dogs, sheep and primates, have been used as animal models in osteoporosis research. Their use enhanced our understanding on the etiology of osteoporosis. Additionally, many therapeutic regimes have entered clinical practice after evaluation on animal models. Experimental protocols leading to bone loss include hormonal interventions (ovariectomy, orchidectomy, hypophysectomy, parathyroidectomy), immobilization, alcohol abuse osteoporosis and osteoporosis induced by food manipulation. Methods of bone mass evaluation, used on animal models, are biochemical markers, densitometry, magnetic resonance imaging, histomorphometry and bone mechanical testing.